Theological Analysis of Christian Religious Education According to the Book of Kings - Simamora, Anrian; Simanjuntak, Binsar; Sitohang, Debora; Nadeak, Devisere; Siburian, Ivan; Pasaribu, Andar Gunawan (Sahabat Publikasi, 2024)
Theology Christian religious education is a science that studies the Lord God in the principles, concepts, and practices of education in the context of Christianity. It includes an understanding of the teachings of Christianity, teaching and learning methodologies that are in line with Christian values, and the application of theological principles in students' education and spiritual development. This study uses an analysis method. The analysis method is a method that explores, observes, and provides understanding based on existing texts and is supported by books related to the discussion. This research aims to find out what Christian Religious Education is like in the context of the Book of Kings. Christian religious education in the context of the Book of Kings emphasizes the understanding that God is sovereign in human life and the importance of practicing the right worship, that is, the object is right, and the way is right. Obedience brings blessings, while rebellion brings condemnation.